Profile of knowledge and attitude literacy for prospective educators through social scientific issues - P S Dewi; I Sukamto; D Rochintaniawati; R Rahmawati; T Agnesa (Pascasarjana Universitas Pendidikan Indonesia, 2020)
A study was conducted to measure the scientific literacy of levwl four students on the theme of learning about global warming. This survey research involved 73 students in two different study programs at Lampung University. Sampling is done by purposive sampling method. Students scientific literacy is measured using tests of knowledge and attitudes developed according to scientific social issues. This test is built under the 2015 PISA framework and is validly used to measure scientific literacy between high achieving and lowachieving university students. The findings show that there are significant differences between the two scientific literacy competencies, namely knowledge and attitude. But the average value of each attitude competency revealed that there were no significant differences between male and female students.